2016
DOI: 10.1111/jce.12914
|View full text |Cite
|
Sign up to set email alerts
|

Bileaflet Mitral Valve Prolapse and Risk of Ventricular Dysrhythmias and Death

Abstract: Although BiMVP is associated with ventricular tachycardia, it is not associated with an increased risk of cardiac arrest/ventricular fibrillation or ICD implantation and is, paradoxically, associated with a better survival compared to SiMVP or matched controls. The findings suggest that, despite its association with ventricular tachycardia, BiMVP in the absence of other risk factors does not seem to portend a poor prognosis at the population level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(26 citation statements)
references
References 13 publications
1
24
0
1
Order By: Relevance
“…In select cohorts (5 patients), preliminary data seem to hint at the reduction, but not complete abolishment, of the burden of malignant arrhythmias and the rate of appropriate shocks following the surgical correction of bileaflet MVP [61], suggesting that multiple factors might be at play. These findings are supported by the more recent data, suggesting that bileaflet MVP in isolation, despite its association with VA, does not seem to portend a poorer prognosis for SCD at the population level [62].…”
Section: Mitral Valve Leaflet Alterationssupporting
confidence: 78%
“…In select cohorts (5 patients), preliminary data seem to hint at the reduction, but not complete abolishment, of the burden of malignant arrhythmias and the rate of appropriate shocks following the surgical correction of bileaflet MVP [61], suggesting that multiple factors might be at play. These findings are supported by the more recent data, suggesting that bileaflet MVP in isolation, despite its association with VA, does not seem to portend a poorer prognosis for SCD at the population level [62].…”
Section: Mitral Valve Leaflet Alterationssupporting
confidence: 78%
“…Interestingly, inferior TWI was present in 77% patients, with intermittent TWI in 58% of AMVP cases. This finding is of importance since TWI is considered a part of the diagnostic tetrad in AMVP [3,4,9]. The observed variability, however, may be also related to cardiac memory.…”
Section: Resultsmentioning
confidence: 80%
“…Several characteristics of the arrhythmogenic MVP (AMVP) were found, including bileaflet MVP, female sex, T-wave inversions (TWI), mitral annular disjunction (MAD), focal fibrosis of papillary muscles (PMs) and adjacent inferobasal LV wall, and frequent/complex ventricular arrhythmias (VA) [1,3,4]. The cohorts studied in MVP series included SCD victims [2,4,6], survivors of cardiac arrest (CA) [3], patients with frequent and complex VA referred for catheter ablation [7,8], or imaging studies for MR [9]. Little is known, however, about the characteristics of patients diagnosed with AMVP in real-life settings.…”
Section: Introductionmentioning
confidence: 99%
“…However, some patients, usually young and without any significant comorbidities, experience malignant ventricular arrhythmias (VA) and sudden cardiac death (SCD), estimated in 0.2-0.4% per year, and up to 1.8% per year in the presence of a flail leaflet [1,2]. Several studies have identified some risk factors associated with malignant arrhythmias and SCD in MVP patients, mainly (i) female sex, (ii) bi-leaflet prolapse, (iii) mitral annulus abnormalities such as dilatation and disjunction (defined as a separation between the left atrial (LA) wall at the level of the valve junction with the LV free wall), (iv) electrocardiographic repolarization abnormalities specifically on the inferolateral leads [3][4][5], (v) frequent and complex premature ventricular contractions (PVCs), and (vi) presence of myocardial fibrosis at the level of the papillary muscles [6,7]. However, it is still largely unknown how to risk-stratify these patients and no specific recommendations have been proposed to help the clinical decision-making.…”
Section: Introductionmentioning
confidence: 99%